The anxiety of influence unbound. Shelley’s Prometheus and Philippide’s Prometheus in the looking glass - Ciutacu, Sorin (Swedish Journal of Romanian Studies, 2024)
The paper draws a brief parallel between the works of Percy Bysshe Shelley Prometheus Unbound (1820) and of the Romanian Alexandru Philippide The Banishment of Prometheus (1922). It starts from the Greek writers’ image of Prometheus in Hesiod’s Works and Days and Theogony and in Aeschylus’ Prometheus Unbound. It also discusses Harold Bloom’s theory as it analyses the potential anxiety of influence of the Greek writers on Shelley and Philippide and it shows forth this effect seen as a “revisionary ratio” and named by Bloom (1973) a tessera, which means “completion and antithesis”. Both authors create a complex Prometheus character who holds multiple facets. Both authors shape Prometheus as a figure that contains the Western core of values, be they positive or negative. Prometheus actually commits the original sin for man’s sake. This haughty act can be compared to the biblical theft of forbidden knowledge. The author claims that the aim of this theft and the punishment meted out to Prometheus by Zeus are destined to estrange man from nature and from God and to push man into hubris. These also kindle man’s Faustian propensity which turns man into his own divinity, or which recasts the divinity according to man’s own design. If Shelley’s Prometheus turns out to be the Romantic hero achieving moral and intellectual perfection, being uplifted by authentic, selfless and noble goals, Philippide’s Prometheus is the disillusioned, bitter hero from a well-wrought ars poetica, who seeks another mankind on whom to bestow his love and selfless goodwill gestures. His poem represents a symbol of the artist living in his ivory tower failing to be understood by his fellow beings.